2007
DOI: 10.1104/pp.107.096685
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genetic Mapping inBoechera stricta, a Close Relative of Arabidopsis

Abstract: The angiosperm family Brassicaceae contains both the research model Arabidopsis (Arabidopsis thaliana) and the agricultural genus Brassica. Comparative genomics in the Brassicaceae has largely focused on direct comparisons between Arabidopsis and the species of interest. However, the reduced genome size and chromosome number (n 5 5) of Arabidopsis complicates comparisons. Arabidopsis shows extensive genome and chromosome reshuffling compared to its close relatives Arabidopsis lyrata and Capsella rubella, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 72 publications
6
94
0
Order By: Relevance
“…Phylogenetic reconstructions showed that both ACK-like parental genomes (i.e., paralogous gene copies a1 and a2) of the Australian mesopolyploids are nested within the paraphyletic tribe Camelineae and the closely related Boechereae. It was shown that karyotypes of all so far analyzed taxa from three tribes of Lineage I (Camelineae, Boechereae, and Descurainieae) resemble or were derived from the ACK (Figure 4; Lysak et al, 2006 and references therein; Schranz et al, 2007;Roosens et al, 2008). Here, we showed that species of two other Camelineae genera (Crucihimalaya and Transberingia), considered as potential parental genomes of the Australian species, descended from the ACK.…”
Section: A Common Allopolyploid Ancestor?supporting
confidence: 58%
See 2 more Smart Citations
“…Phylogenetic reconstructions showed that both ACK-like parental genomes (i.e., paralogous gene copies a1 and a2) of the Australian mesopolyploids are nested within the paraphyletic tribe Camelineae and the closely related Boechereae. It was shown that karyotypes of all so far analyzed taxa from three tribes of Lineage I (Camelineae, Boechereae, and Descurainieae) resemble or were derived from the ACK (Figure 4; Lysak et al, 2006 and references therein; Schranz et al, 2007;Roosens et al, 2008). Here, we showed that species of two other Camelineae genera (Crucihimalaya and Transberingia), considered as potential parental genomes of the Australian species, descended from the ACK.…”
Section: A Common Allopolyploid Ancestor?supporting
confidence: 58%
“…However, the two parental genomes while having the ACK-like structure could already have deviated by chromosome number. Chromosome number reductions from n = 8 to n = 7 to 4 occurred repeatedly in Brassicaceae Schranz et al, 2007;Mandá ková and Lysak, 2008; this study).…”
Section: Evolutionary Scenario Of the Mesopolyploid Wgd Eventsupporting
confidence: 52%
See 1 more Smart Citation
“…We chose 69 loci located on linkage groups 2-7 of the B. stricta genetic map (Schranz et al 2007b). Loci on linkage group 1 (LG1) were not selected because this chromosome showed low levels of recombination in the mapping population (Schranz et al 2007b).…”
Section: Samplingmentioning
confidence: 99%
“…We chose 69 loci located on linkage groups 2-7 of the B. stricta genetic map (Schranz et al 2007b). Loci on linkage group 1 (LG1) were not selected because this chromosome showed low levels of recombination in the mapping population (Schranz et al 2007b). Primers were designed using either PRIMER3 or PRIMACLADE software (Rozen and Skaletsky 2000;Gadberry et al 2005), and the length of the PCR products ranged from 600 to 800 bp.…”
Section: Samplingmentioning
confidence: 99%